Correlation analysis of element contents and mechanical characteristics of shale reservoirs: A case study in the Cen'gong block, South China. (March 2018) - Liu, Jinshou; Ding, Wenlong; Wang, Ruyue; Yang, Haimeng; Wang, Xinghua; Li, Ang
Abstract: The mechanical parameters of shale are some of the most significant assessment indices for shale gas exploitation. The development of element logging offers an opportunity to study the correlations between the elemental concentrations and the mechanical characteristics of shale. Using the Lower Cambrian shale in the Cen'gong area, Guizhou Province, China, as an example, 490 data sets are extracted using formation element and mineralogy (FEM) and cross multipole array acoustic (XMAC) logging. Through Spearman correlation analysis, the correlations between the major elements (Si, Ca, Fe, S, Ti, Mn, Mg, Al, and K) and the mechanical parameters (Young's modulus, Poisson's ratio, shear strength, shear modulus, and brittleness index) are studied. The effects of the Si content on the mechanical parameters (positive/negative correlations, magnitude and significance of the correlations) are discussed based on X-ray diffraction analyses of the minerals in 146 samples. When 1.84% < CSi (Si content) < 28.08%, Young's modulus and the brittleness index decrease with increasing Si content, and Poisson's ratio increases. When 28.08% < CSi < 31.32%, there is no significant correlation between the Si content and the mechanical parameters. When 31.32% < CSi < 44.24%, Young's modulus and the brittleness index increase with increasing Si content, and Poisson's ratio decreases. Thus, it is not reasonable to determine the mechanical properties of shale based only on the elemental composition in different regions. Highlights: The data show correlations between the elemental contents and mechanical parameters. It is inadequate to use only the elemental composition to determine the mechanical properties of shale. Different elemental contents have distinct effects on the rock mechanical parameters.